2015
DOI: 10.1103/physrevb.92.195140
|View full text |Cite
|
Sign up to set email alerts
|

Instability towards staggered loop currents in the three-orbital model for cuprate superconductors

Abstract: We present evidence for the existence of a spontaneous instability towards an orbital loop-current phase in a multiorbital Hubbard model for the CuO2 planes in cuprates. Contrary to the previously proposed θII phase with intra-unit cell currents, the identified instability is towards a staggered pattern of intertwined current loops. The orbitally resolved current pattern thereby shares its staggered character with the proposal of d-density wave order. The current pattern will cause a Fermi surface reconstructi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…The Emery model has been studied using several different numerical approaches: exact diagonalization [23,24], cluster perturbation theory [25], generalized random phase approximation [26], quantum Monte Carlo [27][28][29], density matrix renormalization group [30] and dynamical mean field theory or its cluster generalizations [31]. Here we use the CP-AFQMC method [13,14], which controls the fermion sign problem with a CP approximation that can be systematically improved via a self-consistency procedure [15].…”
mentioning
confidence: 99%
“…The Emery model has been studied using several different numerical approaches: exact diagonalization [23,24], cluster perturbation theory [25], generalized random phase approximation [26], quantum Monte Carlo [27][28][29], density matrix renormalization group [30] and dynamical mean field theory or its cluster generalizations [31]. Here we use the CP-AFQMC method [13,14], which controls the fermion sign problem with a CP approximation that can be systematically improved via a self-consistency procedure [15].…”
mentioning
confidence: 99%
“…However, it can be shown that the order parameter D induces a staggered pattern of currents flowing through the lattice. The current between the lattice sites i and j is given by 124 :…”
Section: Phase Diagram For a Simplified Modelmentioning
confidence: 99%
“…Many theories for potential candidates of the pseudogap "hidden" order were proposed in the literature in order to try to resolve the above-mentioned discrepancies with the experiments (see, e.g., [25][26][27][28][29][30][31] ). We will not detail those works here, but rather focus on the question whether the Θ II -loop-current order suggested by Ref.…”
Section: Introductionmentioning
confidence: 99%